2011
DOI: 10.3390/molecules16021776
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Phage-Displayed Libraries of Peptides during Panning and Amplification

Abstract: Abstract:The amplification of phage-displayed libraries is an essential step in the selection of ligands from these libraries. The amplification of libraries, however, decreases their diversity and limits the number of binding clones that a screen can identify. While this decrease might not be a problem for screens against targets with a single binding site (e.g., proteins), it can severely hinder the identification of useful ligands for targets with multiple binding sites (e.g., cells). This review aims to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
171
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(183 citation statements)
references
References 126 publications
(177 reference statements)
9
171
0
Order By: Relevance
“…S4A). The identification of just hnRNPA2 by conventional phage display screening underscores one of its main limitations, namely the retrieval of very few candidates, likely because many bona fide targets fail to be properly amplified or selected through multiple biopanning rounds (33). The results here presented show that PD-Seq overcomes this shortcoming, providing an opportunity for the high-throughput identification of smallmolecule targets.…”
Section: Significancementioning
confidence: 87%
“…S4A). The identification of just hnRNPA2 by conventional phage display screening underscores one of its main limitations, namely the retrieval of very few candidates, likely because many bona fide targets fail to be properly amplified or selected through multiple biopanning rounds (33). The results here presented show that PD-Seq overcomes this shortcoming, providing an opportunity for the high-throughput identification of smallmolecule targets.…”
Section: Significancementioning
confidence: 87%
“…In previous publications, the result from sequencing of ~100 phage clones suggested that the amplification process enriches for specific peptide sequences [15,16]. Large scale sequencing, however, can provide observations that could not be interpreted from the sequence of 100 clones [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has enabled the discovery of ligands for hundreds of targets, yet the literature still contains several poorly-explained observations: (1) identical sequences could emerge from unrelated screens for unrelated target [22,23], and (2) screens that should yield a large number of diverse ligand often yield only one sequence motif (reviewed in [16]). The nearly complete sequence coverage of libraries illuminates the origin of these observations.…”
Section: Introductionmentioning
confidence: 99%
“…Phages with growth advantage can be not only noise but also decrease the library diversity and lead to a loss of useful mimotopes. Simulations and experiments showed that subtle differences in growth rate yielded drastic differences in clone abundances after rounds of amplifications (Derda, et al, 2011). Thus, propagation-related TUP may even dominate the biopanning results.…”
Section: Data Cleaning Toolsmentioning
confidence: 99%
“…They appear in the biopanning results because they are selected by contaminants or other components of the screening system rather than the target (Menendez & Scott, 2005;Vodnik, et al, 2011). Propagation-related TUP makes another category (Brammer, et al, 2008;Derda, et al, 2011;Thomas, et al, 2010). They sneak into the output of biopanning because they have a higher infection rate or faster secretion rate.…”
Section: Data Cleaning Toolsmentioning
confidence: 99%